ANALYSIS OF IMPACT THE MODERN MARKET TOWARD RETAILERS IN PASAR BERIMAN TOMOHON - Runtu, Marseila Esterlita; Pangemanan, Sifrid S.; Tumbuan, Willem J.F.A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: There are two types of markets, namely modern markets and traditional markets. Modern market is a place where people can buy goods with comfortable and clean. The traditional market can be defined as a meeting place for sellers and buyers. As for the society market as a place for social interaction and market is also the economic backbone of the community. This research was conducted in Pasar Beriman Tomohon. The objectives are to determine the impact of modern market presence towards retailers in Pasar Beriman Tomohon. This research is a descriptive research with qualitative methodology. The population in this study is retailers of Pasar Beriman Tomohon. 10 respondents were chosen as samples. These results indicate that the presence of modern market does not significantly affect retailers in Pasar Tomohon, only retailers clothing and cosmetics experiencing the impact of the modern market presence. For traditional market retailers in order to increase the quality of the product, they must keep their cleanliness and friendliness so that consumers are interested and more convenient to go shopping in Pasar Beriman Tomohon.Â Keywords: traditional market, modern market, retailers